Sealing sheet
By using a sealant layer with a specific epoxy compound and a thermal cationic polymerization initiator, the problems of poor adhesion of the sealant layer at room temperature and deformation during thermosetting are solved, thus achieving good sealing performance.
Patent Information
- Application Number
- CN202080043524.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-06-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-06-12
AI Technical Summary
Existing sealant layers have poor adhesion at room temperature and are prone to deformation during the heat curing process, affecting sealing performance.
The sealant layer contains a specific epoxy compound and a thermo-cationic polymerization initiator to meet the requirements of storage modulus and complex viscosity, ensuring good adhesion at room temperature and resistance to deformation during thermosetting.
It achieves excellent adhesion of the sealant layer at room temperature and shape retention during the thermosetting process, thus improving sealing performance.
Smart Images

Figure DEST_PATH_IMAGE002
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing sheet having a sealing compound layer which has excellent adhesion at room temperature (23° C., hereinafter the same) and is not easily deformed during a thermal curing process. Background Art
[0002] In recent years, organic EL elements have attracted attention as light-emitting elements that can emit light with high brightness by low-voltage direct current driving.
[0003] However, organic EL elements have a problem in that light emission characteristics such as light emission brightness, light emission efficiency, and light emission uniformity are prone to deterioration over time.
[0004] The cause of the problem of reduced light emission characteristics is believed to be that oxygen, water, etc. penetrate into the interior of the organic EL element and deteriorate the electrodes and organic layers. Therefore, a sealing material is used to seal the organic EL element to prevent the penetration of oxygen or water.
[0005] For example, Patent Document 1 describes an image display device sealing material, which is characterized in that it contains a resin component and a curing agent, wherein the resin component contains: an epoxy resin containing a biphenyl skeleton with a weight average molecular weight within a specific range, an epoxy resin containing an alicyclic skeleton with a weight average molecular weight within a specific range, and a styrene-based oligomer with a weight average molecular weight within a specific range.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: WO2018 / 235824. Summary of the invention
[0009] Problems to be solved by the invention
[0010] As described in Patent Document 1, a curable sheet-like adhesive is suitably used as a material for forming a sealant (hereinafter, "a sheet-like adhesive for forming a sealant" may be referred to as a "sealant layer").
[0011] However, some curable sealant layers have poor adhesion at room temperature, and some need to be heated to soften the surface when attached to a sealed object.
[0012] Furthermore, when the sealant layer is thermosetting, the sealant layer, whose fluidity is increased by heating, is deformed by external influences such as vibration in the early stage of the thermosetting process, so that the sealant layer may not be able to exert its inherent sealing performance.
[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a sealing sheet having a sealing agent layer which has excellent adhesion at room temperature and is not easily deformed during a thermal curing process.
[0014] Means for solving problems
[0015] In order to solve the above problems, the present inventors conducted intensive research on a sealant layer containing an epoxy compound. As a result, they found that a sealant layer satisfying the requirements of storage modulus at 23°C and complex viscosity when heated under specified conditions has excellent adhesion at room temperature and is not easily deformed during thermal curing, thereby completing the present invention.
[0016] Therefore, according to the present invention, there are provided the following sealing sheets [1] to
[12] .
[0017] [1] A sealing sheet having a thermosetting sealant layer and satisfying the following requirements (I), (II) and (III):
[0018] Requirement (I): The sealant layer contains one or more epoxy compounds;
[0019] Requirement (II): The storage modulus of the sealant layer at 23°C is 1.3×10 7 Below Pa;
[0020] Requirement (III): When the temperature of the sealant layer is raised from 35°C to 110°C at a rate of 25°C / min and then maintained at 110°C, the complex viscosity of the sealant layer 250 seconds after the start of the temperature rise is 1×10 4 Pa·s or above.
[0021] [2] The sealing sheet described in [1] is characterized in that the sealant layer satisfies the following requirement (IV):
[0022] Requirement (IV): Prepare homogeneous sealant layers [sealant layer (A) and sealant layer (B)], use the sealant layer (A) as a test piece, perform differential scanning calorimetry at a temperature rise rate of 10°C / min at 0°C to 200°C, and calculate the area of the exothermic peak [area (α)], then, after storing the sealant layer (B) at 23°C and a relative humidity of 50% for 7 days, use it as a measurement sample, perform differential scanning calorimetry at a temperature rise rate of 10°C / min at 0°C to 200°C, and calculate the area of the exothermic peak [area ( β )], based on the obtained area value, X calculated by the following formula (1) is 95% or more,
[0023] [Mathematical formula 1]
[0024] X={Area( β ) / area( α )}×100 (1).
[0025] [3] The sealing sheet according to [1] or [2], wherein at least one of the epoxy compounds is a liquid at 25°C.
[0026] [4] The sealing sheet according to [3], wherein the content of the epoxy compound that is liquid at 25° C. is 55% by mass or more based on the entire sealant layer.
[0027] [5] The sealing sheet according to any one of [1] to [4], wherein at least one of the epoxy compounds is an epoxy compound having a glycidyl ether group.
[0028] [6] The sealing sheet according to any one of [1] to [5], wherein at least one of the epoxy compounds is an epoxy compound having an alicyclic skeleton.
[0029] [7] The sealing sheet according to any one of [1] to [6], wherein the sealing agent layer contains a curing agent, and at least one of the curing agents is a thermal cationic polymerization initiator.
[0030] [8] The sealing sheet according to [7], comprising a thermal cationic polymerization initiator as at least one of the curing agents, wherein the thermal cationic polymerization initiator has an exothermic peak temperature of 120° C. or less when subjected to differential scanning calorimetry under the following conditions,
[0031] (Differential Scanning Calorimetry)
[0032] 0.1 parts by mass of a thermal cationic polymerization initiator, 100 parts by mass of bisphenol A diglycidyl ether, 0.1 parts by mass of c A mixture of -butyrolactone was used as a measurement sample and differential scanning calorimetry was performed at 30°C to 300°C at a heating rate of 10°C / min.
[0033] [9] The sealing sheet according to [8], further comprising a thermal cationic polymerization initiator as at least one of the curing agents, wherein the thermal cationic polymerization initiator has an exothermic peak having a peak top temperature exceeding 120° C. when subjected to differential scanning calorimetry under the following conditions,
[0034] (Differential Scanning Calorimetry)
[0035] 0.1 parts by mass of a thermal cationic polymerization initiator, 100 parts by mass of bisphenol A diglycidyl ether, 0.1 parts by mass of c A mixture of -butyrolactone was used as a measurement sample and differential scanning calorimetry was performed at 30°C to 300°C at a heating rate of 10°C / min.
[0036]
[10] The sealing sheet according to any one of [7] to [9], wherein the curing agent is a thermal cationic polymerization initiator.
[0037]
[11] The sealing sheet according to any one of [1] to
[10] , wherein the sealant layer contains a binder resin, and at least one of the binder resins has a glass transition temperature (Tg) of 60° C. or higher.
[0038]
[12] The sealing sheet according to any one of [1] to
[11] , which is used for sealing a light-related device.
[0039] Effects of the Invention
[0040] According to the present invention, there is provided a sealing sheet having a sealing compound layer which is excellent in adhesion at room temperature and is not easily deformed during a thermal curing process. DETAILED DESCRIPTION
[0041] The sealing sheet of the present invention is characterized in that it is a sealing sheet having a thermosetting sealant layer and satisfies the following requirements (I), (II) and (III).
[0042] Requirement (I): The sealant layer contains one or more epoxy compounds.
[0043] Requirement (II): The storage modulus of the sealant layer at 23°C is 1.3×10 7 Below Pa.
[0044] Requirement (III): When the temperature of the sealant layer is raised from 35°C to 110°C at a rate of 25°C / min and then maintained at 110°C, the complex viscosity of the sealant layer 250 seconds after the start of the temperature rise is 1×10 4 Pa·s or above.
[0045] In the present invention, the “sealant layer” means a “sheet-shaped adhesive for forming a sealant.” The cured product of the sealant layer is used as a sealant.
[0046] The sealant layer may be a short strip-shaped layer or a long strip-shaped (belt-shaped) layer.
[0047] [Requirement (I)]
[0048] The sealant layer contains one or more epoxy compounds.
[0049] Since the sealant layer contains the epoxy compound, the sealant layer becomes a thermosetting layer.
[0050] The epoxy compound refers to a compound having at least one, preferably two or more epoxy groups in the molecule. In the present invention, the phenoxy resin described below is not included in the epoxy compound.
[0051] The epoxy group includes groups containing an oxirane structure, such as a glycidyl group, a glycidyl ether group, and an epoxycyclohexyl group.
[0052] The molecular weight of the epoxy compound is usually 100 to 5,000, preferably 200 to 3,000.
[0053] The epoxy equivalent of the epoxy compound is preferably 50 g / eq or more and 1000 g / eq or less, and more preferably 100 g / eq or more and 800 g / eq or less.
[0054] When the epoxy equivalent of the epoxy compound is within the above range, a sealing material (cured product) having high adhesive strength can be formed more efficiently.
[0055] The epoxy equivalent in the present invention refers to a value obtained by dividing the molecular weight by the number of epoxy groups.
[0056] The content of the epoxy compound is preferably 55% by mass or more, more preferably 57 to 75% by mass, based on the entire sealant layer.
[0057] By setting the content of the epoxy compound to 55% by mass or more based on the entire sealant layer, a sealant having high adhesive strength can be formed more efficiently.
[0058] Examples of the epoxy compound include aliphatic epoxy compounds (excluding alicyclic epoxy compounds), aromatic epoxy compounds, and alicyclic epoxy compounds.
[0059] Examples of the aliphatic epoxy compound include monofunctional epoxy compounds such as glycidyl ethers of aliphatic alcohols and glycidyl esters of alkyl carboxylic acids;
[0060] Polyfunctional epoxy compounds such as polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts thereof, and polyglycidyl esters of aliphatic long-chain polyacids.
[0061] Representative compounds of these aliphatic epoxy compounds include alkenyl glycidyl ethers such as allyl glycidyl ether; alkyl glycidyl ethers such as butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and C12-13 mixed alkyl glycidyl ether; 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol tetraglycidyl ether, dipentaerythritol hexaglycidyl ether, polyethylene glycol diglycidyl ether, polyol triglycidyl ether, polyol tetra ... Glycidyl ethers of polyols such as diglycidyl ether of glycol and diglycidyl ether of polypropylene glycol; polyglycidyl ethers of polyether polyols obtained by adding one or more alkylene oxides to aliphatic polyols such as propylene glycol, trimethylolpropane, glycerol, etc.; diglycidyl esters of aliphatic long-chain dibasic acids; monoglycidyl ethers of aliphatic higher alcohols, glycidyl esters of higher fatty acids, epoxidized soybean oil, octyl epoxystearate, butyl epoxystearate, epoxidized polybutadiene, etc.
[0062] Moreover, as an aliphatic epoxy compound, a commercial item can also be used. Commercially available products include: Denacol EX-121, Denacol EX-171, Denacol EX-192, Denacol EX-211, Denacol EX-212, Denacol EX-313, Denacol EX-314, Denacol EX-321, Denacol EX-411, Denacol EX-421, Denacol EX-512, Denacol Denacol EX-861, DenacolEX-911, Denacol EX-941, Denacol EX-920, Denacol EX-931 (all manufactured by Nagase ChemteX);
[0063] Epolight M-1230, Epolight 40E, Epolight 100E, Epolight 200E, Epolight 400E, Epolight 70P, Epolight 200P, Epolight 400P, Epolight 1500NP, Epolight 1600, Epolight 80MF, Epolight 100MF (all manufactured by Kyoeisha Chemical Co., Ltd.);
[0064] Adeka Glycirol ED-503, Adeka Glycirol ED-503G, Adeka Glycirol ED-506, Adeka Glycirol ED-523T (the above are manufactured by ADEKA Company).
[0065] Examples of the aromatic epoxy compound include phenols having at least one aromatic ring, such as phenol, cresol, and butylphenol, and mono- / polyglycidyl ethers of alkylene oxide adducts thereof; and epoxy compounds having an aromatic heterocycle.
[0066] Representative examples of these aromatic epoxy compounds include glycidyl ethers of bisphenol A, bisphenol F, or compounds obtained by further adding alkylene oxides thereto, or epoxy novolac resins;
[0067] Mono- / polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol;
[0068] Glycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups such as phenyl dimethanol, phenyl diethanol, and phenyl dibutyl alcohol;
[0069] Glycidyl esters of polybasic aromatic acid compounds having two or more carboxylic acids such as phthalic acid, terephthalic acid, and trimellitic acid, glycidyl esters of benzoic acid, styrene oxide, or epoxides of divinylbenzene;
[0070] Epoxy compounds having a triazine skeleton such as 2,4,6-tris(glycidyloxy)-1,3,5-triazine, and the like.
[0071] In addition, as the aromatic epoxy compound, commercially available products can also be used. Examples of commercially available products include Denacol EX-146, Denacol EX-147, Denacol EX-201, Denacol EX-203, Denacol EX-711, Denacol EX-721, Oncoat EX-1020, Oncoat EX-1030, Oncoat EX-1040, Oncoat EX-1050, Oncoat EX-1051, Oncoat EX-1010, Oncoat EX-1011, and Oncoat 1012 (all manufactured by Nagase ChemteX Co., Ltd.);
[0072] Ogsol PG-100, Ogsol EG-200, Ogsol EG-210, Ogsol EG-250 (all manufactured by Osaka Gas Chemical Co., Ltd.);
[0073] HP4032, HP4032D, HP4700 (all manufactured by DIC Corporation);
[0074] ESN-475V (All manufactured by Nippon Steel Chemical & Material Co., Ltd.);
[0075] JER (formerly Epikote) YX8800 (all manufactured by Mitsubishi Chemical);
[0076] Marproof G-0105SA, Marproof G-0130SP (both manufactured by NOF Corporation);
[0077] Epiclon N-665, Epiclon HP-7200 (both manufactured by DIC Corporation);
[0078] EOCN-1020, EOCN-102S, EOCN-103S, EOCN-104S, XD-1000, NC-3000, EPPN-501H, EPPN-501HY, EPPN-502H, NC-7000L (all manufactured by Nippon Kayaku Co., Ltd.);
[0079] Adeka Resin EP-4000, Adeka Resin EP-4005, Adeka Resin EP-4100, AdekaResin EP-4901 (the above are manufactured by ADEKA Company);
[0080] TECHMORE VG-3101L (made by Printec);
[0081] TEPIC-FL, TEPIC-PAS, TEPIC-UC (all manufactured by Nissan Chemical Co., Ltd.), etc.
[0082] Examples of the alicyclic epoxy compound include polyglycidyl ethers of polyols having at least one alicyclic structure, and cyclohexene oxide- or cyclopentene oxide-containing compounds obtained by epoxidizing a cyclohexene or cyclopentene ring-containing compound using an oxidizing agent.
[0083] Representative compounds of these alicyclic epoxy compounds include hydrogenated bisphenol A diglycidyl ether, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-1-methylcyclohexyl-3,4-epoxy-1-methylhexanecarboxylate, 6-methyl-3,4-epoxycyclohexylmethyl-6-methyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-3-methylcyclohexylmethyl-3,4-epoxy-3-methylcyclohexanecarboxylate, 3,4-epoxy-5-methylcyclohexylmethyl-3,4-epoxy-5-methylcyclohexanecarboxylate, Hexanecarboxylate, bis(3,4-epoxycyclohexylmethyl) adipate, 3,4-epoxy-6-methylcyclohexanecarboxylate, methylenebis(3,4-epoxycyclohexane), propane-2,2-diyl-bis(3,4-epoxycyclohexane), 2,2-bis(3,4-epoxycyclohexyl)propane, dicyclopentadiene diepoxide, ethylenebis(3,4-epoxycyclohexanecarboxylate), dioctyl epoxyhexahydrophthalate, di-2-ethylhexyl epoxyhexahydrophthalate, 1-epoxyethyl-3,4-epoxycyclohexane, 1,2-epoxy-2-epoxyethylcyclohexane, α -Pinene oxide, limonene dioxide, etc.
[0084] In addition, as alicyclic epoxy compounds, commercially available products can also be used. As commercially available products, Celloxide 2021P, Celloxide 2081, Celloxide 2000, Celloxide 3000 (manufactured by Daicel Corporation); Epolite 4000 (manufactured by Kyoeisha Chemical Co., Ltd.); YX8000, YX8034 (manufactured by Mitsubishi Chemical Corporation); Adeka Resin EP-4088S, Adeka Resin EP-4088L, Adeka Resin EP-4080E (manufactured by ADEKA Corporation), etc. can be cited.
[0085] These epoxy compounds can be used alone or in combination of two or more.
[0086] At least one of the epoxy compounds is preferably a liquid at 25°C.
[0087] “Liquid at 25° C.” means having fluidity at 25° C. The epoxy compound preferably has a viscosity of 2 to 10,000 mPa·s as measured at 25° C. and 1.0 rpm using an E-type viscometer.
[0088] By using an epoxy compound that is liquid at 25° C., it is easy to form a sealant layer that satisfies the requirement (II).
[0089] When the sealant layer contains an epoxy compound that is liquid at 25° C., the content is preferably 55 to 70% by mass, more preferably 57 to 65% by mass, based on the entire sealant layer, from the viewpoint of preventing the sealant layer from adhering to an unintended object at the end.
[0090] When the content of the epoxy compound that is liquid at 25° C. is 55% by mass or more based on the entire sealant layer, it is easy to form a sealant layer that satisfies the requirement (II).
[0091] At least one of the epoxy compounds is preferably an epoxy compound having a glycidyl ether group.
[0092] Since the reactivity of a glycidyl ether group is not that high compared with an epoxycyclohexyl group or the like, a sealing sheet having more excellent storage stability can be obtained by using an epoxy compound having a glycidyl ether group.
[0093] When the sealant layer contains an epoxy compound having a glycidyl ether group, the content thereof is preferably 90% by mass or more, more preferably 95 to 100% by mass, based on the total amount of the epoxy compound.
[0094] By setting the content of the epoxy compound having a glycidyl ether group to be 90% by mass or more based on the total amount of the epoxy compounds, a sealing sheet having more excellent storage stability can be obtained.
[0095] At least one of the epoxy compounds is preferably an epoxy compound having an alicyclic skeleton.
[0096] By using an epoxy compound having an alicyclic skeleton, a curing reaction by cationic polymerization easily proceeds, and a sealing compound layer having a low relative dielectric constant and excellent colorless transparency can be easily formed.
[0097] When the sealant layer contains an epoxy compound having an alicyclic skeleton, the content thereof is preferably 80% by mass or more, more preferably 90 to 100% by mass, based on the total amount of the epoxy compound.
[0098] When the content of the epoxy compound having an alicyclic skeleton is 80% by mass or more relative to the total amount of the epoxy compound, the curing reaction by cationic polymerization easily proceeds, and a sealing agent layer having a low relative dielectric constant and excellent colorless transparency is easily formed.
[0099] [Requirement (II)]
[0100] The storage modulus of the sealant layer at 23°C is 1.3×10 7 Below Pa.
[0101] Since the storage modulus of the sealant layer at 23°C is 1.3×10 7 Pa or less, the sealant layer has excellent adhesion at room temperature.
[0102] The storage modulus of the sealant layer at 23°C is preferably 1.1×10 7 Pa or less, more preferably 1.0×10 7 Below Pa.
[0103] The lower limit of the storage modulus of the sealant layer at 23°C is not particularly limited as long as the sealant layer can maintain a certain shape. The storage modulus of the sealant layer at 23°C is generally 5.0×10 4 Pa or more. In addition, from the viewpoint of preventing the sealant layer from adhering to an undesired object at the end, the storage modulus of the sealant layer at 23°C is preferably 3.0×10 5 Pa or more, more preferably 9.5×10 5 Pa or above.
[0104] The storage modulus of the sealant layer at 23° C. can be measured according to the method described in Examples.
[0105] As the amount of the liquid component in the sealant layer increases, the storage modulus of the sealant layer at 23° C. tends to decrease.
[0106] Therefore, by adjusting the state (solid, liquid) of the epoxy compound to be used or the content thereof, a sealant layer satisfying requirement (II) can be efficiently formed.
[0107] [Requirement (III)]
[0108] When the sealant layer was heated from 35°C to 110°C at a rate of 25°C / min and then maintained at 110°C, the complex viscosity of the sealant layer 250 seconds after the start of the temperature increase (hereinafter, the complex viscosity under such measurement conditions may be referred to as "complex viscosity (Y)") was 1×10 4 Pa·s or above.
[0109] By setting the complex viscosity (Y) to 1×10 4Pa·s or more, the curing reaction is initiated at an early stage of the thermal curing process. Therefore, the sealant layer of the sealing sheet of the present invention is cured without undergoing a state in which fluidity is increased due to a temperature rise, and is therefore less likely to deform in the thermal curing process.
[0110] The complex viscosity (Y) is preferably 1×10 4 ~1×10 6 Pa·s, more preferably 1×10 5 ~1×10 6 Pa·s.
[0111] The complex viscosity (Y) can be measured according to the method described in Examples.
[0112] As the epoxy compound reacts at a lower temperature, the value of the complex viscosity (Y) becomes larger.
[0113] Therefore, by adjusting the type or amount of the curing agent according to the reactivity of the epoxy compound used, a sealant layer satisfying the requirement (III) can be efficiently formed.
[0114] For example, as described later, by using a low-temperature reactive thermal cationic polymerization initiator as a curing agent, the value of the complex viscosity (Y) can be increased.
[0115] [Requirement (IV)]
[0116] The sealant layer preferably satisfies the following requirement (IV).
[0117] Requirement (IV): Prepare homogeneous sealant layers [sealant layer (A) and sealant layer (B)], use sealant layer (A) as a test piece, perform differential scanning calorimetry at 0°C to 200°C at a heating rate of 10°C / min, and calculate the area of the exothermic peak [area ( α )]. The sealant layer (B) was then stored at 23°C and a relative humidity of 50% for 7 days, and then used as a measurement sample. Differential scanning calorimetry was performed at 0°C to 200°C at a heating rate of 10°C / min to determine the area of the exothermic peak [area ( β )]. Based on the obtained area value, X calculated by the following formula (1) is 95% or more.
[0118] [Mathematical formula 2]
[0119] X={Area( β ) / area( α )}×100 (1)
[0120] Here, "homogeneous sealant layers" refer to multiple sealant layers having substantially the same composition and physical properties. For example, two sealant layers obtained by cutting one sealant layer into two are equivalent to homogeneous sealant layers [sealant layer (A) and sealant layer (B)]. In addition, even if two sealant layers are not collected from one sealant layer, but are respectively collected from other sealant layers, two sealant layers collected from sealant layers sold as products with the same manufacturing number are also equivalent to homogeneous sealant layers [sealant layer (A) and sealant layer (B)].
[0121] In addition, "the area of the exothermic peak" means the area of the region surrounded by the base line obtained from the portion other than the exothermic peak of the DSC curve and the DSC curve.
[0122] The sealant layer (A) and the sealant layer (B) are preferably sealant layers close to the state of the sealant layer immediately after production of the sealing sheet.
[0123] Therefore, after the sealing sheet is produced and before the above measurement is performed, the sealant layer (A) and the sealant layer (B) are preferably stored at -30 to +10°C, more preferably at -15 to +5°C.
[0124] As described above, the sealant layer of the sealing sheet of the present invention satisfies the requirement (III).
[0125] However, the sealant layer satisfying the requirement (III) may undergo a curing reaction at a relatively low temperature, and the storage stability may be deteriorated.
[0126] In this regard, the sealant layer satisfying the requirement (IV) hardly undergoes a curing reaction even when stored for 7 days in an environment of 23° C. and a relative humidity of 50%, and is excellent in storage stability.
[0127] By using an epoxy compound having a glycidyl ether group as the epoxy compound or adjusting the amount of the curing agent according to the reactivity of the curing agent, a sealant layer satisfying the requirement (IV) can be efficiently formed.
[0128] [Curing agent]
[0129] The sealant layer may contain a curing agent. When the sealant layer contains a curing agent, the curability of the sealant layer can be further improved.
[0130] The curing agent is not particularly limited as long as it is a curing agent that initiates a curing reaction, but it is preferable to use a curing agent that initiates a curing reaction by heating.
[0131] Examples of the curing agent include a thermal cationic polymerization initiator and other curing agents.
[0132] Examples of curing agents other than the thermal cationic polymerization initiator include tertiary amines such as benzylmethylamine and 2,4,6-tris(dimethylaminomethyl)phenol; imidazole compounds such as 2-methylimidazole, 3-ethyl-4-methylimidazole, and 2-heptadecylimidazole; and Lewis acids such as boron trifluoride / monoethylamine complexes and boron trifluoride / piperazine complexes.
[0133] The curing agent can be used alone or in combination of two or more.
[0134] The content of the curing agent is not particularly limited, but is preferably 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the epoxy compound.
[0135] The sealant layer preferably contains a thermal cationic polymerization initiator as at least one type of curing agent.
[0136] By using a thermal cationic polymerization initiator, it is easy to control the curability of the sealant layer at around room temperature, and the sealant layer satisfying the requirement (III) can be formed more efficiently.
[0137] The thermal cationic polymerization initiator is a compound that generates cationic species that initiate polymerization by heating.
[0138] Examples of the thermal cationic polymerization initiator include sulfonium salts, quaternary ammonium salts, phosphonium salts, diazonium salts, and iodonium salts.
[0139] Examples of the sulfonium salt include triphenylsulfonium tetrafluoroborate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluoroarsenate, tri(4-methoxyphenyl)sulfonium hexafluoroarsenate, diphenyl(4-phenylthiophenyl)sulfonium hexafluoroarsenate, (4-acetoxyphenyl)methyl(2-methylbenzyl)sulfonium tetrakis(pentafluorophenyl)borate, (4-hydroxyphenyl)methyl(4-methylbenzyl)sulfonium tetrakis(pentafluorophenyl)borate, (4-acetoxyphenyl)benzyl(methyl)sulfonium tetrakis(pentafluorophenyl)borate, and benzyl(4-hydroxyphenyl)(methyl)sulfonium tetrakis(pentafluorophenyl)borate.
[0140] As the sulfonium salt, commercially available products can also be used. Examples of commercially available products include: Adeka Opton SP-150, Adeka Opton SP-170, Adeka Opton CP-66, Adeka Opton CP-77 (manufactured by Asahi Electric Corporation), San-Aid SI-60L, San-Aid SI-80L, San-Aid SI-100L, San-Aid SI-B2A, San-Aid SI-B3, San-Aid SI-B3A, San-Aid SI-B7 (manufactured by Sanshin Chemical Co., Ltd.), CYRACURE UVI-6974, CYRACURE UVI-6990 (manufactured by Union Carbide Corporation), UVI-508, UVI-509 (manufactured by General Electric Corporation), FC-508, FC-509 (manufactured by Minnesota Mining & Manufacturing Corporation), CD-1010, CD-1011 (All of the above are manufactured by Sartomer), CI series products (manufactured by Nippon Soda Co., Ltd.), etc.
[0141] Examples of the quaternary ammonium salt include tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate, tetrabutylammonium hydrogen sulfate, tetraethylammonium tetrafluoroborate, tetraethylammonium p-toluenesulfonate, N,N-dimethyl-N-benzylanilinium hexafluoroantimonate, N,N-dimethyl-N-benzylanilinium tetrafluoroborate, N,N-dimethyl-N-benzylopyridinium hexafluoroantimonate, N,N-diethyl-N-benzyl trifluoromethanesulfonate, N,N-dimethyl-N-(4-methoxybenzyl)pyridinium hexafluoroantimonate, and N,N-diethyl-N-(4-methoxybenzyl)toluidinium hexafluoroantimonate.
[0142] Examples of the phosphonium salt include ethyltriphenylphosphonium hexafluoroantimonate and tetrabutylphosphonium hexafluoroantimonate.
[0143] Examples of the diazonium salt include AMERICURE (manufactured by American Can Co., Ltd.) and ULTRASET (manufactured by Asahi Denka Co., Ltd.).
[0144] Examples of the iodonium salt include diphenyliodonium hexafluoroarsenate, bis(4-chlorophenyl)iodonium hexafluoroarsenate, bis(4-bromophenyl)iodonium hexafluoroarsenate, and phenyl(4-methoxyphenyl)iodonium hexafluoroarsenate. In addition, commercially available products include UV-9310C (manufactured by Toshiba Silicone Co., Ltd.), Photoinitiator 2074 (manufactured by Rhone-Poulenc Co., Ltd.), UVE series products (manufactured by General Electric Co., Ltd.), and FC series products (manufactured by Minnesota Mining & Manufacturing Co., Ltd.).
[0145] The thermal cationic polymerization initiator can be used alone or in combination of two or more.
[0146] The sealant layer preferably contains a thermal cationic polymerization initiator (hereinafter sometimes referred to as "thermal cationic polymerization initiator (P)") having an exothermic peak having a peak top temperature of 120° C. or less when subjected to differential scanning calorimetry under the following conditions.
[0147] (Differential Scanning Calorimetry Conditions)
[0148] 0.1 parts by mass of a thermal cationic polymerization initiator, 100 parts by mass of bisphenol A diglycidyl ether, 0.1 parts by mass of c A mixture of -butyrolactone was used as a measurement sample and differential scanning calorimetry was performed at 30°C to 300°C at a heating rate of 10°C / min.
[0149] The thermal cationic polymerization initiator (P) is a thermal cationic polymerization initiator with low temperature reactivity. Therefore, the sealant layer containing the thermal cationic polymerization initiator (P) easily satisfies the requirement (III). As the thermal cationic polymerization initiator (P), there can be listed: (4-acetoxyphenyl) methyl (2-methylbenzyl) sulfonium tetrakis (pentafluorophenyl) borate, (4-hydroxyphenyl) methyl (4-methylbenzyl) sulfonium tetrakis (pentafluorophenyl) borate, (4-acetoxyphenyl) benzyl (methyl) sulfonium tetrakis (pentafluorophenyl) borate. In addition, as a commercial product of the thermal cationic polymerization initiator (P), there can be listed: San-Aid SI-B2A, San-Aid SI-B3A, San-Aid SI-B7 (the above are manufactured by Sanshin Chemical Co., Ltd.).
[0150] When the sealant layer contains a thermal cationic polymerization initiator (P), it preferably further contains a thermal cationic polymerization initiator having an exothermic peak top temperature exceeding 120° C. when subjected to differential scanning calorimetry under the above conditions (hereinafter sometimes referred to as “thermal cationic polymerization initiator (Q)”).
[0151] The thermal cationic polymerization initiator (Q) is a thermal cationic polymerization initiator with high temperature reactivity. Therefore, the sealant layer containing the thermal cationic polymerization initiator (Q) easily satisfies the requirement (IV). From the viewpoint that the temperature during the curing of the sealant layer will not become too high, the peak top temperature of the above-mentioned exothermic peak of the thermal cationic polymerization initiator (Q) is preferably below 170°C. As the thermal cationic polymerization initiator (Q), there can be cited: benzyl (4-hydroxyphenyl) (methyl) sulfonium tetrakis (pentafluorophenyl) borate. In addition, as a commercially available product of the thermal cationic polymerization initiator (Q), there can be cited: San-Aid SI-B3 (manufactured by Sanshin Chemical Co., Ltd.).
[0152] When the sealant layer contains a thermal cationic polymerization initiator (P) and a thermal cationic polymerization initiator (Q), the weight ratio [thermal cationic polymerization initiator (P): thermal cationic polymerization initiator (Q)] is preferably 20:80 to 80:20, more preferably 35:65 to 65:35.
[0153] By setting the weight ratio of the thermal cationic polymerization initiator (P) to the thermal cationic polymerization initiator (Q) within the above range, a sealing sheet having a sealing compound layer in which a curing reaction is initiated at an early stage of a thermal curing step and excellent in storage stability can be efficiently obtained.
[0154] In the sealing sheet of the present invention, it is preferred that all curing agents contained in the sealing compound layer are thermal cationic polymerization initiators.
[0155] When a curing agent other than the thermal cationic polymerization initiator is used, the sealant layer may be colored or the transparency of the sealant layer may be reduced.
[0156] On the other hand, when a thermal cationic polymerization initiator is used, such a problem is less likely to occur. Therefore, when the curing agent contained in the sealant layer is entirely a thermal cationic polymerization initiator, a sealant layer excellent in colorlessness and transparency can be efficiently formed.
[0157] [Binder resin]
[0158] The sealant layer may contain a binder resin. The sealant layer containing a binder resin has excellent shape retention and handling properties.
[0159] The weight average molecular weight (Mw) of the binder resin is not particularly limited, but is preferably 10,000 or more, more preferably 10,000 to 1,000,000, and even more preferably 10,000 to 800,000, from the viewpoint of better compatibility with the epoxy compound and excellent shape retention.
[0160] The weight average molecular weight (Mw) of the binder resin can be determined as a standard polystyrene conversion value by performing gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.
[0161] When the sealant layer contains a binder resin, the content of the binder resin (when containing two or more binder resins, the total amount thereof) is preferably 20 to 43% by mass, more preferably 23 to 40% by mass, based on the entire sealant layer.
[0162] When the content of the binder resin is within the above range, a sealant layer having excellent shape retainability and sufficient adhesive strength can be easily obtained.
[0163] The glass transition temperature (Tg) of the binder resin is not particularly limited, but is preferably 60° C. or higher, more preferably 90° C. or higher, and further preferably 110° C. or higher.
[0164] When the glass transition temperature (Tg) of the binder resin is 60°C or higher, the storage modulus of the cured product of the adhesive layer can be easily increased. In addition, when the glass transition temperature (Tg) of the binder resin is 90°C or higher, a sealant layer having excellent shape retention can be efficiently formed.
[0165] Examples of the binder resin include phenoxy resins, modified olefin resins, and acetal resins.
[0166] Among these, phenoxy resins are preferred as the binder resin from the viewpoint of easily obtaining a sealant layer having excellent shape retaining properties.
[0167] Phenoxy resins are generally equivalent to high molecular weight epoxy resins, and refer to resins having a degree of polymerization of about 100 or more.
[0168] The epoxy equivalent of the phenoxy resin is preferably 5,000 or more, more preferably 7,000 or more. The epoxy equivalent value can be measured in accordance with JIS K7236.
[0169] Examples of the phenoxy resin include bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol S type phenoxy resin, copolymer type phenoxy resin of bisphenol A type and bisphenol F type, distillates thereof, naphthalene type phenoxy resin, novolac type phenoxy resin, biphenyl type phenoxy resin, and cyclopentadiene type phenoxy resin.
[0170] These phenoxy resins can be used alone or in combination of two or more.
[0171] The phenoxy resin can be obtained by a method of reacting a bifunctional phenol with an epihalohydrin to a high molecular weight, or by subjecting a bifunctional epoxy resin to a polyaddition reaction with a bifunctional phenol.
[0172] For example, it can be obtained by reacting a bifunctional phenol with an epihalohydrin in the presence of an alkali metal hydroxide in an inert solvent at a temperature of 40 to 120° C. Alternatively, it can be obtained by subjecting a bifunctional epoxy resin to a bifunctional phenol in the presence of a catalyst such as an alkali metal compound, an organic phosphorus compound, a cyclic amine compound, etc., in an organic solvent such as an amide solvent, an ether solvent, a ketone solvent, a lactone solvent, an alcohol solvent, etc. having a boiling point of 120° C. or higher, and heating to 50 to 200° C. at a reaction solid content concentration of 50% by weight or less, and performing a polyaddition reaction.
[0173] The bifunctional phenols are not particularly limited as long as they are compounds having two phenolic hydroxyl groups. Examples thereof include: monocyclic bifunctional phenols such as hydroquinone, 2-bromohydroquinone, resorcinol, and catechol; bisphenols such as bisphenol A, bisphenol F, bisphenol AD, and bisphenol S; dihydroxybiphenyls such as 4,4'-dihydroxybiphenyl; dihydroxyphenyl ethers such as bis(4-hydroxyphenyl)ether; and compounds obtained by introducing straight-chain alkyl groups, branched-chain alkyl groups, aryl groups, hydroxymethyl groups, allyl groups, cyclic aliphatic groups, halogens (tetrabromobisphenol A, etc.), nitro groups, etc. into the aromatic rings of these phenol skeletons; and polycyclic bifunctional phenols obtained by introducing straight-chain alkyl groups, branched-chain alkyl groups, allyl groups, substituted allyl groups, cyclic aliphatic groups, alkoxycarbonyl groups, etc. into the carbon atoms located in the center of these bisphenol skeletons.
[0174] Examples of the epihalohydrin include epichlorohydrin, epibromohydrin, and epiiodohydrin.
[0175] In the present invention, a commercially available product may be used as the phenoxy resin. For example, the products include: YX7200, YL7553, YL6794, YL7213, YL7290, and YL7482 manufactured by Mitsubishi Chemical Co., Ltd., YX8100 manufactured by Mitsubishi Chemical Co., Ltd. (phenoxy resin containing a bisphenol S skeleton), FX280, FX293, and FX293S manufactured by Tohto Chemical Co., Ltd. (phenoxy resin containing a fluorene skeleton), jER1256 and jER4250 manufactured by Mitsubishi Chemical Co., Ltd., YP-50 and YP-50S manufactured by Nippon Steel Chemical & Material Co., Ltd. (both phenoxy resins containing a bisphenol A skeleton), YX6954 manufactured by Mitsubishi Chemical Co., Ltd. (phenoxy resin containing a bisphenol acetophenone skeleton), and ZX-1356-2 manufactured by Nippon Steel Chemical & Material Co., Ltd.
[0176] [Silane coupling agent]
[0177] The sealant layer may contain a silane coupling agent. By containing a silane coupling agent, it is easier to obtain a sealant layer with better wet heat durability.
[0178] As the silane coupling agent, known silane coupling agents can be used, among which organic silicon compounds having at least one alkoxysilyl group in the molecule are preferred.
[0179] Examples of the silane coupling agent include silane coupling agents having a (meth)acryloyl group such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane;
[0180] Silane coupling agents having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, diethoxymethylvinylsilane, trichlorovinylsilane, and vinyltri(2-methoxyethoxy)silane;
[0181] Silane coupling agents having epoxy groups, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 8-glycidoxyoctyltrimethoxysilane;
[0182] Silane coupling agents having a styryl group, such as p-styryltrimethoxysilane and p-styryltriethoxysilane;
[0183] Silane coupling agents having an amino group such as N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl / butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and the hydrochloride of N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane;
[0184] Silane coupling agents having urea groups, such as 3-ureidopropyltrimethoxysilane and 3-ureidopropyltriethoxysilane;
[0185] Silane coupling agents having halogen atoms such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane;
[0186] Silane coupling agents having a mercapto group, such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane;
[0187] Silane coupling agents having a sulfide group such as bis(trimethoxysilylpropyl)tetrasulfide and bis(triethoxysilylpropyl)tetrasulfide;
[0188] Silane coupling agents having an isocyanate group, such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane;
[0189] Silane coupling agents having allyl groups, such as allyltrichlorosilane, allyltriethoxysilane, and allyltrimethoxysilane;
[0190] Silane coupling agents having a hydroxyl group, such as 3-hydroxypropyltrimethoxysilane and 3-hydroxypropyltriethoxysilane, etc.
[0191] These silane coupling agents can be used alone or in combination of two or more.
[0192] When the sealant layer contains a silane coupling agent, the content of the silane coupling agent in the entire sealant layer is preferably 0.01 to 5% by mass, more preferably 0.05 to 1% by mass.
[0193] [Other ingredients]
[0194] The sealant layer may contain other components within a range not hindering the effects of the present invention.
[0195] Examples of other components include additives such as ultraviolet absorbers, antistatic agents, light stabilizers, antioxidants, resin stabilizers, fillers, pigments, extenders, and softeners.
[0196] These other components can be used alone or in combination of two or more.
[0197] When the sealant layer contains these additives, the content thereof can be appropriately determined according to the purpose.
[0198] [Sealing agent layer]
[0199] The thickness of the sealant layer is usually 1 to 50 m m, preferably 1 to 25 m m, more preferably 5 to 25 m The sealant layer having a thickness within the above range is suitable for use as a material for forming a sealing material.
[0200] The thickness of the sealant layer can be measured using a known thickness gauge in accordance with JIS K 7130 (1999).
[0201] The method for forming the sealant layer is not particularly limited, and the sealant layer may be formed, for example, by casting.
[0202] When the sealant layer is produced by casting, a sealant composition containing components constituting the sealant layer is prepared, the obtained sealant composition is applied to a substrate or a release layer of a release film that has been subjected to release treatment by a known method, and the obtained coating is dried to form the sealant layer.
[0203] The sealant composition may contain a solvent.
[0204] Examples of the solvent include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, butanone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; alicyclic hydrocarbon solvents such as cyclopentane, cyclohexane and methylcyclohexane, etc.
[0205] These solvents can be used alone or in combination of two or more.
[0206] The content of the solvent can be appropriately determined in consideration of coating properties and the like.
[0207] Examples of a method for applying the sealant composition include spin coating, spray coating, bar coating, knife coating, roll coating, doctor blade coating, die coating, and gravure coating.
[0208] Examples of a method for drying the coating film include conventionally known drying methods such as hot air drying, hot roll drying, and infrared irradiation.
[0209] The conditions for drying the coating film are, for example, 80 to 150° C. for 30 seconds to 5 minutes.
[0210] The sealant layer has a thermosetting property. That is, when the sealant layer is heated, at least the epoxy group of the epoxy compound reacts and the sealant layer is cured.
[0211] The conditions for thermally curing the sealant layer are not particularly limited.
[0212] The heating temperature is usually 80 to 200°C, preferably 90 to 150°C.
[0213] The heating time is usually 30 minutes to 12 hours, preferably 1 to 6 hours.
[0214] The storage modulus of the sealant cured material layer obtained by curing the sealant layer at 90°C is preferably 1×10 8 Pa or more, more preferably 1×10 9 ~1×10 11 Pa. Since the storage modulus at 90°C is 1×10 8The sealant cured material layer with a value of Pa or more has excellent sealing properties and is therefore more suitable as a sealing material. In addition, after the sealant cured material layer is formed, it is easy to prevent the sealant cured material layer from being damaged or peeled off in the process for manufacturing a device sealed body.
[0215] [Sealing sheet]
[0216] The sealing sheet of the present invention has the above-mentioned sealant layer.
[0217] The sealing sheet of the present invention may have a substrate, a release film, a functional film, and the like in addition to the sealant layer.
[0218] As the substrate, a resin film is generally used.
[0219] Examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, cycloolefin polymer, aromatic polymer, and polyurethane polymer.
[0220] The thickness of the substrate is not particularly limited, but is preferably 10 to 500 μm. m m, more preferably 10 to 300 m m, more preferably 15 to 200 m m.
[0221] The release film functions as a support in the production process of the sealing sheet, and also functions as a protective sheet for the sealant layer until the sealing sheet is used.
[0222] It should be noted that when the sealing sheet of the present invention is used, the release film is usually peeled off and removed.
[0223] As the release film, a conventionally known release film can be used, and for example, a release film having a release layer subjected to a release treatment with a release agent on a release film substrate can be mentioned.
[0224] Examples of the release film substrate include paper substrates such as glassine paper, coated paper, and premium paper; laminated paper obtained by laminating a thermoplastic resin such as polyethylene on these paper substrates; and plastic films such as polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, polypropylene resin, and polyethylene resin.
[0225] Examples of the release agent include rubber elastomers such as silicone-based resins, olefin-based resins, isoprene-based resins, and butadiene-based resins, long-chain alkyl-based resins, alkyd-based resins, and fluorine-based resins.
[0226] The thickness of the release film is not particularly limited, but is generally 20 to 250 μm. m m or so.
[0227] When the sealing sheet of the present invention has a release film, the release film may be provided one each on both sides of the sealant layer, or two in total, or the release film may be provided only on one side of the sealant layer.
[0228] Examples of the functional film include conductive films, gas barrier films, antireflection films, phase difference films, viewing angle enhancement films, brightness enhancement films, etc. Among these, for example, as the gas barrier film, a film having a metal film or an inorganic compound film can be mentioned.
[0229] The thickness of the functional film is not particularly limited, but is usually 5 to 200 μm. m m, preferably 10 to 100 m m.
[0230] The sealant layer of the sealing sheet of the present invention is suitably used as a material for forming a sealing material for electronic devices. Among electronic devices, light-related devices such as light-emitting devices, light-receiving devices, and display devices are preferred.
[0231] Examples of light-related devices include organic EL elements such as organic EL displays and organic EL lighting; liquid crystal elements such as liquid crystal displays; electronic paper elements; solar cell elements; and light-emitting diodes.
[0232] The method of sealing an electronic device using the sealing sheet of the present invention is not particularly limited. For example, the sealing agent layer of the sealing sheet of the present invention may be attached to a target electronic device, and then the sealing agent layer may be cured by the above method to seal the electronic device. Example
[0233] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to the following examples.
[0234] [Compounds used in Examples or Comparative Examples]
[0235] Epoxy compound (A1): hydrogenated bisphenol A type epoxy resin [manufactured by Mitsubishi Chemical Co., Ltd., trade name: YX8000, epoxy equivalent: 205 g / eq];
[0236] Epoxy compound (A2): 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate [manufactured by Daicel, trade name: Celloxide 2021P, epoxy equivalent: 128 to 145 g / eq];
[0237] Phenoxy resin (B1): (manufactured by Mitsubishi Chemical Co., Ltd., trade name: YX7200B35, glass transition temperature (Tg): 150° C.);
[0238] Thermal cationic polymerization initiator (C1): (4-hydroxyphenyl)methyl(4-methylbenzyl)sulfoniumtetrakis(pentafluorophenyl)borate (manufactured by Sanshin Chemical Co., Ltd., trade name: San-Aid SI-B7);
[0239] Thermal cationic polymerization initiator (C2): benzyl(4-hydroxyphenyl)(methyl)sulfoniumtetrakis(pentafluorophenyl)borate (manufactured by Sanshin Chemical Co., Ltd., trade name: San-Aid SI-B3);
[0240] Silane coupling agent (D1): 8-glycidoxyoctyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM4803).
[0241] [Evaluation of Reactivity of Thermal Cationic Polymerization Initiator]
[0242] 0.1 parts by mass of a thermal cationic polymerization initiator (C1), 100 parts by mass of bisphenol A diglycidyl ether (jER828 manufactured by Mitsubishi Chemical Co., Ltd.), 0.1 parts by mass of c When a mixture of -butyrolactone was used as a measurement sample and differential scanning calorimetry was performed at 30 to 300°C at a heating rate of 10°C / min, the peak top temperature of the exothermic peak was 105°C.
[0243] On the other hand, when the thermal cationic polymerization initiator (C2) was used instead of the thermal cationic polymerization initiator (C1), the peak top temperature of the exothermic peak was 140°C.
[0244] [Example 1]
[0245] 170 parts by mass of the epoxy compound (A1), 100 parts by mass of the phenoxy resin (B1), 1.5 parts by mass of the thermal cationic polymerization initiator (C1), 1.5 parts by mass of the thermal cationic polymerization initiator (C2), and 0.2 parts by mass of the silane coupling agent (D1) were dissolved in methyl ethyl ketone to prepare a coating liquid.
[0246] The coating liquid was applied to the release-treated surface of a release film (first release film, manufactured by Lintec, trade name: SP-PET752150), and the resulting coating film was dried at 100° C. for 2 minutes to form a film having a thickness of 15 m The release-treated surface of a release film (second release film, manufactured by Lintec, trade name: SP-PET381130) was further bonded to the sealant layer to obtain a sealant sheet.
[0247] [Examples 2 to 3, Comparative Examples 1 and 2]
[0248] Except having changed the kind and amount of each component which comprises a sealant layer into the kind and amount described in Table 1, it carried out similarly to Example 1, and obtained the sealing sheet.
[0249] The following tests were conducted on the sealing sheets obtained in Examples 1 to 3 and Comparative Examples 1 and 2. The results are shown in Table 1.
[0250] [Measurement of storage modulus of sealant layer at 23°C]
[0251] The sealant layers of the sealing sheets obtained in Examples and Comparative Examples were laminated at 23° C. using a laminator to obtain test pieces having a thickness of about 1 mm.
[0252] The storage modulus of the obtained test piece was measured using a dynamic viscoelasticity measuring apparatus (manufactured by Anton Paar, trade name: Physica MCR301) at a frequency of 1 Hz, a strain of 1%, a heating rate of 3°C / min, and a range of -20 to 150°C. The measurement results at 23°C are shown in Table 1.
[0253] [Evaluation of the adhesion of the sealant layer to the sealed object]
[0254] The sealing sheets obtained in the examples and comparative examples were cut to obtain test pieces with a width of 50 mm and a length of 150 mm. The second release film of the obtained test piece was peeled off, and the exposed sealant layer was overlapped with an alkali-free glass plate under the conditions of a temperature of 23°C and a relative humidity of 50%, and a pressure of 0.5 MPa was applied using a pressure roller. The state of the sealant layer floating from the alkali-free glass plate was observed, and the case where no floating occurred was evaluated as A, and the case where floating occurred was evaluated as B.
[0255] [Complex viscosity of the sealant layer during temperature rise]
[0256] The sealant layers of the sealing sheets obtained in Examples and Comparative Examples were laminated under the conditions of 23° C. and a relative humidity of 50% to obtain a test piece having a thickness of about 1 mm.
[0257] The complex viscosity of the obtained test piece was measured in the range of 35 to 110°C using a dynamic viscoelasticity measuring apparatus (manufactured by TA Instrument, trade name: ARES) at a frequency of 1 Hz, a strain of 0.1%, and a heating rate of 25°C / min (maintained at 110°C after reaching 110°C).
[0258] Table 1 shows the complex viscosity of the test piece 250 seconds after the start of the temperature rise.
[0259] [Evaluation of shape retention of sealant layer during thermal curing]
[0260] The second release film of the sealing sheet obtained in Examples and Comparative Examples was peeled off, and the exposed sealant layer was attached to an alkali-free glass plate, and then cut into a size of 50 mm in width×50 mm in length to obtain a test piece.
[0261] The first release film was peeled off from the test piece, and the exposed sealant layer was overlapped on a non-alkali glass plate under the conditions of a temperature of 23° C. and a relative humidity of 50%, and a pressure of 0.5 MPa was applied using a pressure roller to obtain a laminate.
[0262] Then, the laminate was heat-pressed under the conditions of 0.5 MPa and 110° C. The laminate was evaluated as A when the sealant layer of the laminate after heat-pressing was not deformed, and evaluated as B when the sealant layer was deformed with an enlarged area.
[0263] [Evaluation of storage stability of sealant layer]
[0264] Two sealing sheets each obtained in Examples and Comparative Examples were prepared.
[0265] The sealant layer of one of the sealing sheets was used as a test piece A, and differential scanning calorimetry was performed at 0°C to 200°C at a heating rate of 10°C / min (using an apparatus: DSC Q2000 manufactured by TA Instruments), and the peak area of the exothermic peak [area ( α )].
[0266] Another sealing sheet was stored at 23° C. and a relative humidity of 50% for 7 days. The sealant layer of the sealing sheet was used as a test piece B and the differential scanning calorimetry was performed in the same manner to determine the peak area of the exothermic peak [area ( β )].
[0267] The area ( β ) and area( α The case where the ratio of ) is 95% or more is evaluated as A, and the case where it is less than 95% is evaluated as B.
[0268] [Table 1]
[0269]
[0270] The following results can be seen from Table 1.
[0271] The sealant layer of the sealing sheets obtained in Examples 1 to 3 was excellent in adhesion at 23° C. and was not easily deformed during the thermal curing process.
[0272] On the other hand, the sealant layer of the sealing sheet obtained in Comparative Example 1 did not contain a thermal cationic polymerization initiator having low-temperature reactivity, and therefore did not satisfy requirement (III) of the present invention. Therefore, it easily flowed during the thermal curing process and had poor shape retention.
[0273] Moreover, the sealant layer of the sealing sheet obtained in Comparative Example 2 did not satisfy the requirement (II) of the present invention and therefore had poor adhesion at 23°C.
[0274] Furthermore, the sealing compound layer of the sealing sheet obtained in Comparative Example 2 contained a thermal cationic polymerization initiator having low-temperature reactivity and did not contain an epoxy compound having a glycidyl ether group. Therefore, the storage stability of the sealing sheet was poor.
Claims
1. A sealing sheet, characterized in that: It is a sealing sheet having a heat-curable sealant layer. The sealant layer contains a curing agent, and the curing agent is a thermal cationic polymerization initiator. At least one of the curing agents is a thermal cationic polymerization initiator having a peak top temperature of an exothermic peak of 120° C. or less when a differential scanning calorimetry is performed at 30° C. to 300° C. at a heating rate of 10° C. / min using a mixture of 0.1 parts by mass of a thermal cationic polymerization initiator, 100 parts by mass of bisphenol A diglycidyl ether, and 0.1 parts by mass of γ-butyrolactone as a measurement sample, The sealant layer contains a binder resin, and at least one of the binder resins has a glass transition temperature (Tg) of 60° C. or higher. and meets the following requirements (I), (II) and (III), Requirement (I): The sealant layer contains one or more epoxy compounds, and at least one of the epoxy compounds is an epoxy compound that is liquid at 25°C, the content of the epoxy compound that is liquid at 25°C is 55% by mass or more relative to the entire sealant layer, and at least one of the epoxy compounds is an epoxy compound having a glycidyl ether group; Requirement (II): The storage modulus of the sealant layer at 23°C is 1.3×10 7 Below Pa; Requirement (III): When the temperature of the sealant layer is raised from 35°C to 110°C at a rate of 25°C / min and then maintained at 110°C, the complex viscosity of the sealant layer 250 seconds after the start of the temperature rise is 1×10 4 Pa·s or above.
2. The sealing sheet according to claim 1, characterized in that: The sealant layer satisfies the following requirement (IV): Requirement (IV): A sealant layer A and a sealant layer B of the same quality are prepared, and the sealant layer A is used as a test piece, and differential scanning calorimetry is performed at a temperature increase rate of 10°C / min at 0°C to 200°C to obtain the area (α) of the exothermic peak. Then, after the sealant layer B is stored at 23°C and a relative humidity of 50% for 7 days, it is used as a measurement sample and differential scanning calorimetry is performed at a temperature increase rate of 10°C / min at 0°C to 200°C to obtain the area (β) of the exothermic peak. Based on the obtained area value, X calculated by the following formula (1) is 95% or more: X={area(β) / area(α)}×100(1).
3. The sealing sheet according to claim 1, wherein: At least one of the epoxy compounds is an epoxy compound having an alicyclic skeleton.
4. The sealing sheet according to claim 1, further comprising a thermal cationic polymerization initiator as at least one of the curing agents, wherein the thermal cationic polymerization initiator has a peak top temperature of an exothermic peak exceeding 120°C when subjected to differential scanning calorimetry under the following conditions: (Differential Scanning Calorimetry) A mixture of 0.1 parts by mass of a thermal cationic polymerization initiator, 100 parts by mass of bisphenol A diglycidyl ether, and 0.1 parts by mass of γ-butyrolactone was used as a measurement sample, and differential scanning calorimetry was performed at 30° C. to 300° C. at a heating rate of 10° C. / min. The sealing sheet according to claim 1 , which is used for sealing light-related devices.
Citation Information
Patent Citations
Image display device sealing material and image display device sealing sheet
WO2018235824A1
Method for manufacturing adhesive composition, adhesive composition and adhesive tape
CN102702988A
Adhesive composition, anisotropic conductive film, and semiconductor device using same
CN106661411A
Cation-curable resin composition
CN108291012A
Semiconductor mounting resin composition and semiconductor mounting resin composition sheet comprising the same, and semiconductor device using the same and production method thereof
JP2015209477A